No reward—no effort : Will Bitcoin collapse near to the year 2140? - Grobys, Klaus (Elsevier, 2024)
This paper explores whether the overall evolution of Bitcoin log-prices would manifest a log-period power-law singularity (LPPLS) signature, eventually resulting in the arrival of a finite-time singularity. Calibrating the LPPLS model using daily data on Bitcoin covering the 2011—2023 period, this study indeed finds evidence for a strong LPPLS signature suggesting the arrival of a spontaneous singularity in the year 2129. Further striking evidence suggests that Bitcoin will experience what we term a close-to-singularity-condition near to the year 2050—a remarkable coincidence with the recently documented arrival of a finite-time singularity in U.S. equities.
Keywords: Bitcoin; Bubble; Collapse; Expected value; Log-periodicity; Finite-time singularity; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|